Not All Clear Air Turbulence Is Kolmogorov—The Fine-Scale Nature of Atmospheric Turbulence - Rodriguez Imazio, Paola Carolina (2023)
We study a strong clear air turbulence (CAT) event experienced by the German High-Altitude Long-Range research aircraft (HALO) during the Southern Hemisphere Transport, Dynamics, and Chemistry campaign. HALO encountered CAT leeward of the southern Andes Mountains, where tropospheric airflow favored vertically propagating mountain waves that were refracted southeastward into the core of tropopause jet. Turbulence is quantified using spectral quantities and structure functions computed from in situ 100 Hz flight level data. The detected CAT region exhibits strong patchiness, characterized by separated bursts in turbulent kinetic energy and energy dissipation rate. The high resolution in situ observations reveal different turbulent scaling within each patch, in both spectra and structure functions, and following Monin and Yaglom's conversion law. One patch follows power laws with exponents −1.71 ± 0.06, −1.771 ± 0.006, and −1.56 ± 0.05 for the velocity components w, v, and u, respectively, while another patch has exponents −2.17 ± 0.12, −2.50 ± 0.08, and −1.92 ± 0.09. These patches are mediated by a third patch with less clear scaling. While the patches can deviate from Kolmogorov scaling due to the anisotropy of the airflow, they still display evidence of CAT with enhanced energy dissipation rates.